PENGELOLAAN OBJEK WISATA BAHARI PANTAI AIR BANGIS DI NAGARI AIR BANGIS KECAMATAN SUNGAI BEREMAS KABUPATEN PASAMAN BARAT TAHUN 2014 - 2015 - Tama, Afandi Hadya; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Marine-based tourism (nautical tourism) has become an attractive tourism product internationally. The Indonesian archipelago has great potential to develop maritime tourism potential.Tourism object of Air Bangis’s beach based on Nagari Air Bangis, Sungai Beremas District,West Pasaman has potential to be managed and developed. Tourism object of Air Bangis’s beach offers its own charm, potential maritime tourism Beach Air Bangis have minimal facilities and infrastructure support. Thus causing this potential has not been managed optimally. The purpose of this research was to determine the management of maritime tourismobjectBeach Air Bangis and to identify the several problems encountered in the management of Maritime Tourism Object of Air Bangis’s beach. This research use a qualitative approach with descriptive research. Observation, documentation and interview were used for data collection techniques. Analysis of the data is limited to data processing techniques or facts obtained to develop categories that are relevant to the purpose of research and interpretation based on the theories accordingly. The results showed that the management of maritime tourism object of Beach Air Bangis not optimally managed, it can be seen from the management function of local government that has not done well, such as planning, organizing, actuating or directing, coordination and controling. There are problems that face by the Department of Culture and Tourism of West Pasaman in the management of maritime tourism object of Beach Air Bangis, including, the lack of regulations governing activities in the field, unoptimal coordination in the management of maritime tourism object of Beach Air Bangis, limited facilities and infrastructure, unoptimal monitoring activities undertaken Department of Culture and tourism, the lack of quality human resources in the field of tourism, and also still low public awareness of the potential of marine tourism in the area. Keywords: Management, Government Management, Marine Tourism